2017
DOI: 10.1001/jamadermatol.2017.0045
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of Posttransplant Dermatologic Diseases by Race

Abstract: IMPORTANCE The risk for skin cancer has been well characterized in white organ transplant recipients (OTRs); however, most patients on the waiting list for organ transplant in the United States are nonwhite. Little is known about cutaneous disease and skin cancer risk in this OTR population. OBJECTIVE To compare the incidence of cutaneous disease between white and nonwhite OTRs. DESIGN, SETTING, AND PARTICIPANTS This retrospective review of medical records included 412 OTRs treated from November 1, 2011, throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 19 publications
1
25
0
Order By: Relevance
“…Lack of screening and poor patient education are thought to be important contributors to poor medical outcomes and have been implicated as significant factors in the increased mortality from genital SCC in the nonwhite population. 2 Similarly, we found a strikingly low awareness of the presence of genital lesions by the entire OTR cohort but noted this deficit irrespective of race/ ethnicity. A total of 92.5% of patients denied having lesions, but nearly half had at least one lesion in the genital area.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Lack of screening and poor patient education are thought to be important contributors to poor medical outcomes and have been implicated as significant factors in the increased mortality from genital SCC in the nonwhite population. 2 Similarly, we found a strikingly low awareness of the presence of genital lesions by the entire OTR cohort but noted this deficit irrespective of race/ ethnicity. A total of 92.5% of patients denied having lesions, but nearly half had at least one lesion in the genital area.…”
Section: Discussionmentioning
confidence: 50%
“…1 The development of SCC in the sun-protected areas of the genital region has been described in OTRs. 2,3 Viral warts are common in OTRs, and human papillomavirus (HPV) has been hypothesized to play a role in the development of genital SCC. In addition, HPV infection is more frequently associated with tumors that develop in OTRs compared with immunocompetent individuals.…”
mentioning
confidence: 99%
“…Though we provided a potential of at least 5 years of follow‐up post transplantation, 19.5% of NAKTRs did not have a single recorded dermatology visit. A recent study comparing White, Asian, Black, and Hispanic SOTRs found that the average time elapsed from transplantation to first SC diagnosis in non‐whites was 7.64 years. Additionally, Buoy et al .…”
Section: Discussionmentioning
confidence: 99%
“…This study found that 5.1% of non‐white KTRs developed KC, of which 73% were cutaneous squamous cell carcinoma (cSCC). Chung et al . found that 41.6% of white SOTRs developed SC compared to 9.9% of non‐white (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the physician should keep patient‐specific risks in mind when referring for screening or performing a FBSE. Genital lesions are often asymptomatic and are more prevalent in non‐Caucasian recipients . Due to the fact that our data for the epidemiology of genital lesions or other cutaneous cancers in SOTR are limited, we did not ask panelists to debate screening recommendations for these diagnoses.…”
Section: Discussionmentioning
confidence: 99%